2015
DOI: 10.1371/journal.pgen.1005415
|View full text |Cite
|
Sign up to set email alerts
|

BMP Inhibition in Seminomas Initiates Acquisition of Pluripotency via NODAL Signaling Resulting in Reprogramming to an Embryonal Carcinoma

Abstract: Type II germ cell cancers (GCC) can be subdivided into seminomas and non-seminomas. Seminomas are similar to carcinoma in situ (CIS) cells, the common precursor of type II GCCs, with regard to epigenetics and expression, while embryonal carcinomas (EC) are totipotent and differentiate into teratomas, yolk-sac tumors and choriocarcinomas. GCCs can present as seminomas with a non-seminoma component, raising the question if a CIS gives rise to seminomas and ECs at the same time or whether seminomas can be reprogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
123
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(133 citation statements)
references
References 86 publications
(150 reference statements)
10
123
0
Order By: Relevance
“…The most parsimonious interpretation of these observations is that the prominent burst of mCpH-pluri in ECs, having already passed through an erased PGC/GCNIS ancestry, represents a reversion to/ reactivation of pluripotency, with de novo apparition. As further evidence for such a recrudescence of pluripotency in ECs, we found that induction of pluripotent EC phenotypes from the seminomatous TCam-2 cell line following xenograft to murine testis (Nettersheim et al 2015) spawns mCpH-pluri (Supplemental Fig. S9C), which we now interpret as a key molecular event previously unrecognized in that experiment.…”
Section: Tgct (Nse) Subtype-specific Methylationsupporting
confidence: 58%
See 1 more Smart Citation
“…The most parsimonious interpretation of these observations is that the prominent burst of mCpH-pluri in ECs, having already passed through an erased PGC/GCNIS ancestry, represents a reversion to/ reactivation of pluripotency, with de novo apparition. As further evidence for such a recrudescence of pluripotency in ECs, we found that induction of pluripotent EC phenotypes from the seminomatous TCam-2 cell line following xenograft to murine testis (Nettersheim et al 2015) spawns mCpH-pluri (Supplemental Fig. S9C), which we now interpret as a key molecular event previously unrecognized in that experiment.…”
Section: Tgct (Nse) Subtype-specific Methylationsupporting
confidence: 58%
“…TGCTs' association with developmental gonadal defects supports the prevailing model by which they originate from a multipotent stem cell arising in the germline, which fails to disable pluripotency to mature into a spermatogonium (McGlynn and Cook 2009;Sheikine et al 2012). On the other hand, recent studies identifying reversion to pluripotency in the germline (Nettersheim et al 2015;Oliveros-Etter et al 2015) question whether TGCTs entail a continuation of, versus reversion to, functional pluripotency.…”
mentioning
confidence: 99%
“…In a previous study, we demonstrated that TCam-2 cells are able to transit into an EC-like state when being xenografted into the flank of nude mice [10]. Analyses revealed that the somatic microenvironment inhibits BMP signaling, which is the initial step in the reprogramming process of TCam-2 cells, leading to induction of NODAL signaling and expression of EC-related genes as well as globally increased 5mC levels ( in vitro : 18 %; 6 weeks in vivo : 70 %) [10].…”
Section: Resultsmentioning
confidence: 99%
“…Analyses revealed that the somatic microenvironment inhibits BMP signaling, which is the initial step in the reprogramming process of TCam-2 cells, leading to induction of NODAL signaling and expression of EC-related genes as well as globally increased 5mC levels ( in vitro : 18 %; 6 weeks in vivo : 70 %) [10]. During this reprogramming, we found a very rapid (after 1 week of in vivo growth) and strong upregulation of the transcription factor SOX2 (Log 2 2.16 fold) and in parallel downregulation of SOX17 (Log 2 3.75 fold) [10]. Due to the importance of SOX2 in cellular reprogramming and maintenance of pluripotency, we were interested in the role of SOX2 in the reprogramming of TCam-2.…”
Section: Resultsmentioning
confidence: 99%
“…Non-seminomas form highly heterogeneous tumors with both differentiated and undifferentiated cells forming teratomas and choriocarcinomas and display more embryonal-like features. Using a seminoma xenograft model in which seminoma cells are reprogrammed to form carcinomas with more embryonal-like features, expression of key pluripotency and chromatin remodeling genes was examined [107]. Nodal was upregulated during this transition by demethylation of the Nodal promoter.…”
Section: Nodal and Cancermentioning
confidence: 99%